2020
DOI: 10.2147/ott.s260376
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emerging Roles and Therapeutic Interventions of Aerobic Glycolysis in Glioma</p>

Abstract: Glioma is the most common type of intracranial malignant tumor, with a great recurrence rate due to its infiltrative growth, treatment resistance, intra-and intertumoral genetic heterogeneity. Recently, accumulating studies have illustrated that activated aerobic glycolysis participated in various cellular and clinical activities of glioma, thus influencing the efficacy of radiotherapy and chemotherapy. However, the glycolytic process is too complicated and ambiguous to serve as a novel therapy for glioma. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 213 publications
(317 reference statements)
0
16
0
Order By: Relevance
“…Glioma is one of the most malignant and aggressive type of primary brain tumor (H. Chen et al, 2019). The prognosis of glioma is poor, despite the progress in therapeutic strategies, including surgery resection, chemotherapy, and radiotherapy (Han et al, 2020). Although the mechanism in the tumorigenesis of glioma remains unclear, the role of circRNAs in cancer development and progression has raised many concerns currently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma is one of the most malignant and aggressive type of primary brain tumor (H. Chen et al, 2019). The prognosis of glioma is poor, despite the progress in therapeutic strategies, including surgery resection, chemotherapy, and radiotherapy (Han et al, 2020). Although the mechanism in the tumorigenesis of glioma remains unclear, the role of circRNAs in cancer development and progression has raised many concerns currently.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard management of GBM is a combined treatment based on surgery and including radiotherapy and chemotherapy. However, due to the infiltrative growth, resistance to therapies, and intra‐ and intertumoral genetic heterogeneity, GBM has a high recurrence rate (W. Han et al, 2020). The results of treatment are still not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that UBE2D3 exerted functions in glioma via SHP-2. Activated glycolysis is reported to be associated with the progression of glioma (24). The blockade of glucose transporters and glycolytic enzymes exhibited promising anticancer effects in preclinical models (15).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main early cellular events evoked upon exposure to hypoxia is the activation of hypoxia-inducible factor 1 (HIF-1) [ 5 ], an oxygen-regulated transcription factor that mediates the adaptation of cells to decreased oxygen supply. On the other hand, accumulating studies have demonstrated that accelerated aerobic glycolysis, also known as the Warburg effect, participates in the clinical aggressiveness of tumors including gliomas [ 6 ]. In contrast to normal cells, malignant cells use pyruvate for energy production instead of fluxing it into acetyl-CoA in the tricarboxylic acid (TCA) cycle, even under normoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of glucose metabolism through aerobic glycolysis is higher, so the production of lactate from glucose occurs much faster than the complete oxidation of glucose in the TCA cycle at the expense of inefficient ATP production [ 7 ]. As a result, cancer cells overexpress glucose transporters to compensate for their high energy demand with their abnormally high rate of glucose uptake [ 6 ].…”
Section: Introductionmentioning
confidence: 99%